Structure, Prohibitions, and Stages in Saibatin Traditional Marriage: An Ethnographical and Legal Study - Widiyanti, Alzahra (Jurnal Terekam Jejak, 2025)
This study discusse~s the~ structure~, prohibitions, and stage~s of Saibatin customary marriage~ in Lampung as part of a sustainable~ customary le~gal syste~m. Using a normative~ and e~thnographic juridical approach through inte~rvie~ws, lite~rature~ studie~s, and fie~ld docume~ntation, it was found that Saibatin customary marriage~ include~s the~ matudau (hone~st) and se~me~nda syste~ms, with prohibitions re~late~d to kinship and social status. The~ stage~s include~ pre~-marriage~, the~ main ce~re~mony, and the~ closing with the~ awarding of the~ adok title~. Its imple~me~ntation is in line~ with national law as long as it doe~s not conflict with Law No. 1 of 1974. Saibatin customs function not only as a cultural tradition, but also as a le~gal syste~m that maintains harmony and moral value~s ​​in Lampung socie~ty.